Embolization of Atrial Septal Defect Occluder Device into the Left Ventricle- Emergency Surgical Removal - Raha, Sanjay Kumar; Sarker, Swadesh Ranjan; Ahmed, ATS; Islam, Md Zahidul; Karim, Md Rezaul; Hasan, Md Kamrul (University Heart Journal, 2015)
With the introduction of technological improvements, invasive cardiologic interventions have become increasingly used alternatives to surgery. Despite its numerous benefits, serious and potentially life-threatening complications of invasive cardiology interventions may occur. We presented a case of attempted percutaneous transcatheter closure of a large ASD in 6 years old boy, complicated by device embolization to the left ventricle necessitating emergency surgical retrieval in the department of cardiac surgery, National Institute of Cardiovascular Diseases (NICVD), Dhaka. University Heart Journal Vol. 10, No. 2, July 2014; 95-96